Noise-induced Hearing Loss among Non-Medical Workers in a Healthcare Institution - Mammen, Manju Deena; Augustine, Ann Mary; Lepcha, Anjali; Sharma, Jessie Sophia; Prakash, Arockiaraj Arul; Philip, Ajay (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: The effects of prolonged and excessive noise exposure on healthcare workers have not been studied. This study aims to estimate the prevalence of hearing loss among such workers and correlate the degree of hearing loss with age, duration of exposure, and coexisting illnesses. Methods: A retrospective review of 117 clinical records was conducted on 179 employees working in areas of excessive noise in a tertiary care hospital. Correlations between categorical variables were made using the Chi-square and Fisher's exact tests, while an independent samples t-test was used to compare means for continuous variables. Binary logistic regression was used to quantify the strength of correlations through an odds ratio and 95% confidence interval. Results: A clinical evaluation was conducted to assess hearing loss on employees from various departments, including Boiler Section, Central Sterile Supply Department (CSSD), Laundry, Prosthetics and Orthotics Laboratory, and Dietary. The median age of the participants was 37 years. Out of the 116 participants who underwent by audiological tests, 63.8% had sensorineural hearing loss and 68.5% had absent otoacoustic emissions in at least one frequency. The incidence of hearing loss was found to increase with age (p = 0.037). A significant correlation was noted between hearing loss and the duration of noise exposure of more than 10 years (p = 0.0013). Considering all areas together, a significantly higher proportion of employees with hearing loss was observer (p = 0.044), with 69.5% in the CSSD. Conclusion: Noise-induced hearing loss is a prevalent occupational health hazard in healthcare settings. The risk of developing hearing loss increases with the duration of work in a noise-generating area.